Improving Employee Engagement Through HRM Practices in Public Hospitals - Ma’arof, Rabiatul Adawiyah; Rashid, Umi Kartini; Nasuredin, Juzaimi (Advances in Social Sciences Research Journal, 2023)
The objective of this study is to examine the relationship between Human Resource Management (HRM) practices and employee engagement within the context of nurses in public hospitals in Malaysia. Prior studies have investigated several factors that influence employee engagement in Malaysia. However, the present study specifically concentrates on examining the relationship between HRM practices and employee engagement. The study encompassed a sample of 330 nurses employed in public hospitals in Malaysia. Data analysis was performed using Statistical Package for Social Sciences (SPSS) software version 25. The study revealed that the implementation of three specific HRM practices, namely career development, employee participation, and training and development, had a positive and significant effect on employee engagement. The findings have the potential to offer useful insights to decision-makers within healthcare organizations in Malaysia. Specifically, these insights can inform the development of effective HRM strategies aimed at enhancing employee engagement among nurses. Moreover, this study offers suggestions for future research and recommendations for the authorities to strengthen human resource policies pertaining to the healthcare sector in Malaysia.